1998
DOI: 10.1029/97wr03606
|View full text |Cite
|
Sign up to set email alerts
|

Effect of enhanced manganese oxidation in the hyporheic zone on basin‐scale geochemical mass balance

Abstract: Abstract. We determined the role of the hyporheic zone (the subsurface zone where stream water and shallow groundwater mix) in enhancing microbially mediated oxidation of dissolved manganese (to form manganese precipitates) in a drainage basin contaminated by copper mining. The fate of manganese is of overall importance to water quality in Pinal Creek Basin, Arizona, because manganese reactions affect the transport of trace metals. The basin-scale role of the hyporheic zone is difficult to quantify because str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
279
2

Year Published

2000
2000
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 262 publications
(292 citation statements)
references
References 35 publications
7
279
2
Order By: Relevance
“…The 5-to 7-km perennial reach of Pinal Creek relevant to this study is a sand-and gravel-bed stream with an average slope of 1%, an average width of 2.3 m, and an average depth of 15 cm. Pools are almost nonexistent and riffles or cascades are fairly unusual (Harvey and Fuller, 1998). Perennial flow begins about 5-to 7 km upstream of Inspiration Dam ( Fig.…”
Section: Pinal Creek Site Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 5-to 7-km perennial reach of Pinal Creek relevant to this study is a sand-and gravel-bed stream with an average slope of 1%, an average width of 2.3 m, and an average depth of 15 cm. Pools are almost nonexistent and riffles or cascades are fairly unusual (Harvey and Fuller, 1998). Perennial flow begins about 5-to 7 km upstream of Inspiration Dam ( Fig.…”
Section: Pinal Creek Site Descriptionmentioning
confidence: 99%
“…At least three studies have investigated the processes responsible for Mn oxide formation in the hyporheic zone of Pinal Creek. Harvey and Fuller (1998) studied Mn(II) oxidation by hyporheic zone sediments in batch experiments using natural and artificial stream water (pH 7, $0.7 mM Mn 2+ ) in the presence and absence of microbial poisons (NaN 3 , tetracycline, and penicillin). They found that Mn(II) oxidation was strongly enhanced in the presence of microbial activity.…”
Section: Introductionmentioning
confidence: 99%
“…A comparison of transient storage model parameters (obtained from a tracer injection) and observed subsurface flows indicated that the model does not always adequately represent actual stream-subsurface exchange [Harvey et al, 1996]. While existing models employ a single exchange coefficient, in reality, exchange is driven by multiple processes that operate at several spatial scales [Harvey and Bencala, 1993;Harvey and Fuller, 1998;Wroblicky et al, 1998]. Prediction of hyporheic exchange will require improved understanding of the processes that drive transport across the stream-subsurface interface.…”
Section: Introductionmentioning
confidence: 99%
“…It provides conditions within streams for heterotrophic primary production [Mulholland et ] to locations far from the stream channel [Stanford and Ward, 1993], hyporheic flow provides habitat for aquatic macroinvertebrates. Hyporheic flow changes surface water quality characteristics through physical and biogeochemical processes: physical mixing with groundwater [Constantz, 1998], chemical reactions Harvey and Fuller, 1998], microbially mediated chemical transformations [Duff and Triska, 1990;McMahon and Bohlke, 1996], and transport of nutrients to streams through groundwater-surface water interactions [Wondzell and Swanson, 1996;Valett et al, 1997].…”
Section: Introductionmentioning
confidence: 99%